Edu-PHOTSIC (Education Program for Test of High Order Thinking Skill in Chemistry): Upaya meningkatkan kemampuan peserta didik SMAN 2 Siak Hulu dalam menghadapi ujian nasional - Siti Imroatus Sa'adah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
National examination, as an evaluation of national standard benchmarks to achieve good quality students, should have had questions component with high order thinking skills (HOTS). HOTS questions should be applied in national-level subject such as chemistry. The significance of a lesson related to the daily life activities was still not yet integrated in the learning process comprehensively due to several targets that needed to be completed by the teachers.This kind of problems was experienced by students in SMAN Siak Hulu. According to Puspendik Kemendikbud (2017) that showed the results of National Exam of SMAN Siak Hulu from 2015 up to 2017, it proved that the average scores of Chemistry subject decreased year by year in a row; 78.13 (2015), 63.86 (2016), and 48.33 (2017). This issue signified that HOTS orientation in Chemistry class was still relatively low. Therefore, Community Service (PKM) activities are needed, So that teachers and students could comprehend the HOTS question by joining Edu-PHOTSIC program.Edu-PHOTSIC program was conducted in three phases; preparation phase, implementation phase, and report phase. The results of this program showed that there was an improvement of understanding about the use and implementation of HOTS question by teachers and students.